(untitled) (Altruism: The Indonesian Journal of Community Engagement, 2024)
The problem of inorganic waste in rural areas not only impacts the environment but also reflects the suboptimal utilization of resources with economic value. Furthermore, village households still face limitations in increasing their income. This community service activity aims to empower households through processing inorganic waste into economically valuable craft products in Ridan Permai Village. The methods used included outreach, skills training, production assistance, and simple marketing education. The results of the activity indicate an increase in community knowledge about waste management, enhanced skills in processing waste into creative products, and the emergence of home-based business opportunities. This program has had a positive impact not only on improving the community’s economy but also on environmental awareness.